X-Ray Tests of AISI 430 and 304 Stainless Steels and AISI 1010 Low Carbon Steel Welded by CO2 Laser beam welding - Taskin, Mustafa; Caligulu, Ugur; Turkmen, Mustafa (Carl Hanser Verlag, 2011)
For this study, X-Ray radiographic tests of AISI 430 and 304 stainless steels with AISI 1010 low-carbon steels welded by CO2 Laser beam welding (LBW) have been performed. Laser beam welding experiments were carried out under argon and helium shielding gas, at 2000-2250 and 2500 W heat input and 100-200-300 cm/min welding speeds. After this process, the radiographic tests of the welded joints were performed by X-Ray diffraction. The result of the radiographic tests indicated that with increasing heat input the widths of the deep penetration increased in all specimens. On the contrary, by increasing the welding speeds the widths of the deep penetration decreased. The best properties of the AISI 430 and 304 stainless and AISI 1010 low-carbon steel welds were observed at the specimens welded at 2500 W heat input and 100 cm/min welding speed.
Keywords: Process Temperature; Cast-Iron; Bondability; Ferrite